Basalt powder as alternative fertilizer in black bean crop in Red Oxisol - Silva, Darlan Weber da; Canepelle, Eduardo; Lanzanova, Mastrângello Enívar; Guerra, Divanilde; Redin, Marciel (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The basalt powder (PB) has been used as an alternative nutrient source in some cultures in Brazil, especially grain plants such as black beans. The objective of this study was to evaluate the effect of doses of PB in the production of dry matter of shoot (MSPA) and black beans grains in a Red Oxisol. The experiment was conducted for two experimental years, 2017/18 and 2018/19 harvests in a randomized block design, with three replications, totaling 33 experimental plots, consisting of 6 m² each. The treatments were: 5, 10, 20, 40, 60, 80, 120, 160, 200 t ha-1 of PB, in addition to another treatment with chemical fertilization NPK and a control - TEST (without PB and NPK). The sowing of black beans was 40 cm between rows and 12 cm between plants. At the full flowering stage of the plants, the production of MSPA was determined and at harvest, the grains. The production of MSPA and bean grains showed an increasing trend in relation to the doses of PB, that is, the higher the dose of PB, the greater the production of MSPA and grains, with values ranging from 1091 to 2892 kg ha-1 and 989 to 2111 kg ha-1, respectively. Doses of 5 to 60 t ha-1 have equivalent action on the productivity of MSPA and black bean grains compared to chemical fertilization NPK. PB doses above 80 t ha-1 promote the highest productivity of black bean grains in a Red Oxisol.